Bringing IoT to the Lab: SiLA2 and Open-Source-Powered Gateway Module for Integrating Legacy Devices into the Digital Laboratory. (October 2020) - Porr, Marc; Schwarz, Sebastian; Lange, Ferdinand; Niemeyer, Laura; Hentrop, Thorleif; Marquard, Daniel; Lindner, Patrick; Scheper, Thomas; Beutel, Sascha
Graphical abstract: Abstract: In this article a gateway module to integrate legacy laboratory devices into the network of the digital laboratory in the 21st century is introduced. The device is based on ready to buy consumer hardware that is easy to get and inexpensive. Depending on the specific requirements of the desired application (bare embedded computer, RS232 serial port connector, IP65 certified casing and connectors) the needed investment ranges from about 95 € up to 200 €. The embedded computer runs an open source Linux operating system and can in principle be used to run any kind of software needed for communicating with the laboratory device. Here the open source SiLA2 standard is used for presenting the device's functions in the network. As an example the digital integration of a magnetic stirrer is shown and can be used as a template for other applications. A method for easy remote integration of the device to ensure an easy and consistent workflow in development, testing and usage is also presented. This incorporates a method for remote installation of SiLA2 servers on the box as well as a web frontend for administration, debugging and management of those.